2020
DOI: 10.1002/adma.202006395
|View full text |Cite
|
Sign up to set email alerts
|

Colors of Single‐Wall Carbon Nanotubes

Abstract: that when single-wall CNTs (SWCNTs) are sorted by diameter [7-10] or atomic structure [i.e., (n,m)], [11-14] they strikingly exhibit various distinct colors in suspension. More recently, colorful SWCNT thin films were produced by a novel one-step fabrication procedure, [15] enabling the direct synthesis of colorful SWCNTs that were previously thought impossible. Despite numerous studies on SWCNT colors, the coloration mechanism has not been fully understood. Currently, no theoretical model can reliably predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…These films appeared gray rather than black, as is typically observed with conventional micron-scale SWCNT films. 31 To make paper-based electrodes, we cut the dried SWCNT paper into 24 individual strips (3 × 4 mm), attached these to copper wire with silver paste, and wrapped the assembly with Parafilm (Figure S4). We then deposited platinum nanomaterials onto the SWCNT paper electrodes through either electrochemical reduction of chloroplatinic acid (Figure 1E) or vacuum filtration of a solution of citrate-capped PtNPs (Figure 1F).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These films appeared gray rather than black, as is typically observed with conventional micron-scale SWCNT films. 31 To make paper-based electrodes, we cut the dried SWCNT paper into 24 individual strips (3 × 4 mm), attached these to copper wire with silver paste, and wrapped the assembly with Parafilm (Figure S4). We then deposited platinum nanomaterials onto the SWCNT paper electrodes through either electrochemical reduction of chloroplatinic acid (Figure 1E) or vacuum filtration of a solution of citrate-capped PtNPs (Figure 1F).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The thickness of the SWCNT films with a surface density of 8.3 μg/cm 2 was 160 ± 2 nm (Figure S2B), which demonstrated that a nanoscale-thickness film had formed on the paper surface. These films appeared gray rather than black, as is typically observed with conventional micron-scale SWCNT films . To make paper-based electrodes, we cut the dried SWCNT paper into 24 individual strips (3 × 4 mm), attached these to copper wire with silver paste, and wrapped the assembly with Parafilm (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…The random SWCNT network is ideal for fabricating transparent conductive films [94][95][96][97] because of their small diameter, good optical and electrical properties, and excellent flexibility. Recently, the floating metal catalyst CVD method is developed to achieve high quality, density, and purity SWCNTs deposited on substrate [98][99][100][101][102][103]. The high intertube Schottky junction resistance [103], existence of aggregated bundles of SWCNTs, and performance-yield tradeoff [102] are key issues, which may lead to a degraded electronic and optoelectronic performance of the films.…”
Section: Brief Summary Of Controlled Synthesis Of Cntsmentioning
confidence: 99%
“…Ever since the discovery of CNTs, it has always been a great challenge to render them with various colors. Although single-walled CNTs (SWCNTs) with narrow chirality distribution obtained by separation from mixtures can exhibit some colors, which strongly depend on the chiral structures of SWCNTs (9)(10)(11)(12), this method has serious restrictions and shortcomings. On the one hand, the chirality separation of SWCNTs with narrow distribution is a challenging, sophisticated, and timeconsuming technique that is only suitable for short CNTs (CNT powders) and usually exhibits colors in suspensions, but cannot be used for long CNTs and CNT assemblies such as fibers and films.…”
Section: Introductionmentioning
confidence: 99%